Security relation of Sarawak-West Kalimantan: an analysis/ Muhammad Khairil Fahmi Ab Razak & Warick Mandes - Ab Razak, Muhammad Khairil Fahmi; Mandes, Warick (2014)
What is security? Many define security as a defense from other threat. Security term has a various use for. It could be human security, environmental security, national security, international security and etc. Security is the important matter to everyone so that to ensure the person will be safe from any threat. Same goes to every country has its own security. Therefore each country has its own security policy to protect themselves from any threat from others.